Fiscal deficit of states in India / edited by Janak Raj Gupta - "Gupta,Janak Raj .(ed.)" (New Delhi, 2001)
Ever since the structural adjustment programme of 1991, The concern about the ever growing size of Fiscal deficit has developed. In the early eighties it was only the central Government which was suffering from the malaise of deficit budget, but since then the states have also gone deeper and deeper into the Fiscal crisis so much so that the revenue Expenditure gap which they are experiencing now has become unsustainable. The book provides both a theoretical background and the empirical evidence pertaining to many states in the country insofar as explicit explanation of a deficit budget is concerned. The book illustrates the various concepts of deficit which are currently in vogue, viz., revenue deficit, capital deficit, budget deficit, Fiscal deficit, primary deficit, NET Fiscal deficit, NET primary deficit, monetized deficit, structural deficit, etc. Each concept has its own merits and demerits and for the sound management of state finances, their proper interpretation is the pre-requisite. The various articles published in this book have been written by various economists working in the various universities and research institutes in their chosen field of research. An attempt has been made in this book to identify theoretically as well as empirically the factors which have led to the present stage of impasse in Fiscal crisis both at the centre and at the level of various states. Some articles in the book go even beyond that and try to provide useful solutions both in the Short-Run and in the Long-Run.
Keywords: Deficit budgets